Gc-ms analysis of active compounds of cinnamon leaf extracts (cinnamomum burmanni blume) - ANAK AGUNG KETUT DARMADI,; DEWA NGURAH SUPRAPTA,; I GEDE RAI MAYA TEMAJA,; I MADE DIRA SWANTARA, (International Journal of Pharma and Bio Sciences, 2017)
The plant of the type Cinnamomum burmanni Blume that belongs to the family of Lauraceaein Bali-Indonesia is known as cinnamon. This plant has many benefits namely a specific medicine for impaired digestion, stomach pain with nausea, condiments, and serves as anti-bacterial and fungi. This study was conducted to determine the GC-MS analysis of the methanol extracts of cinnamon leaves. There were ten chemical compounds identified, the dominant chemical compounds were Azulene (CAS) Cylopentacycloheptene (52.5%), Azulene (CAS) Cylopentacycloheptene (21.5%) and Phenol, 2,2'-methylene bis [6- (1 , 1-dimethylethy) -4-ethyl (12.1%).